2022
DOI: 10.3390/horticulturae8020175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drought Stress on Growth and Essential Oil Yield of Ocimum Species

Abstract: A pot experiment was conducted to assess the effect of drought stress on growth and secondary compound accumulation of Ocimum species, in a semi-controlled greenhouse during the year 2020. The experiment was performed as a factorial that was based on a randomized complete design with three species of basil namely O. basilicum ‘Genovese’, O. x africanum, and O. americanum, and three levels of water supply (70, 50, and 30% soil water capacity-SWC) that were replicated twice. The results revealed that severe drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…× africanum plants showed a 19% and a 28% reduction in height and diameter, respectively. Previous studies also showed that water shortage significantly decreases the growth parameters of sweet basil cultivars in different growing areas [17,[24][25][26]. In addition, reduced growth as a result of the drought was also reported on O.…”
Section: Plant Height and Canopy Diametermentioning
confidence: 86%
See 3 more Smart Citations
“…× africanum plants showed a 19% and a 28% reduction in height and diameter, respectively. Previous studies also showed that water shortage significantly decreases the growth parameters of sweet basil cultivars in different growing areas [17,[24][25][26]. In addition, reduced growth as a result of the drought was also reported on O.…”
Section: Plant Height and Canopy Diametermentioning
confidence: 86%
“…In addition, reduced growth as a result of the drought was also reported on O. × africanum [14,17] and O. gratissimum [13,16]. Almost all the evidence revealed that drought restricted the growth of Ocimum species and other medicinal and aromatic plants.…”
Section: Plant Height and Canopy Diametermentioning
confidence: 89%
See 2 more Smart Citations
“…Sweet basil growth and production can be influenced by environmental factors as water stress (Mulugeta and Radácsi, 2022). Water stress have negative effect on photosynthesis, biochemical process, transpiration, stomatal conductance, protein synthesis, antioxidant enzyme activity, osmoprotectants accumulation and biosynthesis of secondary metabolites as volatile oil yield and its constituents.…”
Section: Introductionmentioning
confidence: 99%